(untitled) (Research, Society and Development, 2021)
The National Health Promotion Policy pointed to the explanation of mechanisms that would reduce situations of vulnerability, radically defend equity and incorporate participation and social control in the management of public policies, thus there was an increase in the number of elderly people, among other factors , needing to resume the discussions that permeate the crisis in the health sector. This study aims to discuss the role of the nursing professional in providing health care to the elderly in a perspective of intersectoral and multiprofessional actions to improve the lifestyle of this public. The methodology is of narrative review, through bibliographic survey in secure data sources, without restriction of year of publication of the works. As presented results, it is shown that nurses are extremely important in the multiprofessional team in health units in the development of prevention, promotion and recovery actions for the health of the elderly, in addition to disease prevention. Through a bibliographic survey, it is concluded that in order to have a qualified, resolutive and effective attention to the elderly, it is necessary to train professionals, including nurses, duly qualified to glimpse the tenacity of the installation of pathological processes in the elderly, you can often change them from independent to dependent.